CD4+ and viral load outcomes of antiretroviral therapy switch strategies after virologic failure of combination antiretroviral therapy in perinatally HIV-infected youth in the United States. (23rd October 2015) - Fairlie, Lee; Karalius, Brad; Patel, Kunjal; van Dyke, Russell B.; Hazra, Rohan; Hernán, Miguel A.; Siberry, George K.; Seage, George R.; Agwu, Allison; Wiznia, Andrew
Abstract : Objective: This study compared 12-month CD4 + and viral load outcomes in HIV-infected children and adolescents with virological failure, managed with four treatment switch strategies. Design: This observational study included perinatally HIV-infected (PHIV) children in the Pediatric HIV/AIDS Cohort Study (PHACS) and Pediatric AIDS Clinical Trials (PACTG) Protocol 219C. Methods: Treatment strategies among children with virologic failure were compared: continue failing combination antiretroviral therapy (cART); switch to new cART; switch to drug-sparing regimen; and discontinue all ART. Mean changes in CD4 + % and viral load from baseline (time of virologic failure) to 12 months follow-up in each group were evaluated using weighted linear regression models. Results: Virologic failure occurred in 939 out of 2373 (40%) children. At 12 months, children switching to new cART (16%) had a nonsignificant increase in CD4 + % from baseline, 0.59 percentage points [95% confidence interval (95% CI) −1.01 to 2.19], not different than those who continued failing cART (71%) (−0.64 percentage points, P = 0.15) or switched to a drug-sparing regimen (5%) (1.40 percentage points, P = 0.64). Children discontinuing all ART (7%) experienced significant CD4 + % decline −3.18 percentage points (95% CI −5.25 to −1.11) compared with those initiating new cART ( P = 0.04). All treatment strategies except discontinuing ART yielded significant mean decreases in log10 VL by 12 months, the new cART group having the largest drop (−1.15 log10 VL). Conclusion: In PHIV children with virologic failure, switching to new cART was associated with the best virological response, while stopping all ART resulted in the worst immunologic and virologic outcomes and should be avoided. Drug-sparing regimens and continuing failing regimens may be considered with careful monitoring. Abstract : Supplemental Digital Content is available in the text